2018
DOI: 10.1080/15423166.2018.1470024
|View full text |Cite
|
Sign up to set email alerts
|

Post-Conflict Cooperation in Multi-Ethnic Local communities of Bosnia and Herzegovina: A Qualitative Comparative analysis of Diaspora's Role

Abstract: How are diaspora involvement in peacebuilding and elite cooperation in multi-ethnic municipalities complementary? This article examines how local elites perceive and respond to conflict-generated diaspora's role in peacebuilding in nine post-conflict multi-ethnic municipalities of Bosnia and Herzegovina, and whether these perceptions can determine types of inter-ethnic cooperation within local institutions. Using a systematic comparative case study analysis utilising ideal-type fuzzy set qualitative comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, some researchers in fields such as diaspora studies and international relations attempt to disentangle the also complex migration-conflict nexus. For instance, Hasić (2018) investigates post-conflict co-operation in multi-ethnic local communities in Bosnia and Herzegovina, addressing the question of how the involvement of a diaspora in peacebuilding may complement intra-ethnic co-operation among elites in multi-ethnic municipalities. In another context, Rubenzer (2008) specifically looks at the attributes of ethnic minority interest groups and these groups' influence on U.S. foreign policy.…”
Section: Qca In Development Studiesmentioning
confidence: 99%
“…However, some researchers in fields such as diaspora studies and international relations attempt to disentangle the also complex migration-conflict nexus. For instance, Hasić (2018) investigates post-conflict co-operation in multi-ethnic local communities in Bosnia and Herzegovina, addressing the question of how the involvement of a diaspora in peacebuilding may complement intra-ethnic co-operation among elites in multi-ethnic municipalities. In another context, Rubenzer (2008) specifically looks at the attributes of ethnic minority interest groups and these groups' influence on U.S. foreign policy.…”
Section: Qca In Development Studiesmentioning
confidence: 99%
“…In contested political environments back home, it becomes interesting to examine under which conditions diaspora can provide more opportunity to widen the politics of memory in their homelands. Previous research has demonstrated that diaspora participation in peacebuilding can also create potential competition between diaspora, returnee, and local actors and slow down or change peacebuilding and transitional justice processes (Hasić 2018). A recent volume has examined multiple cases of diaspora coordination, focusing on different ways in which diaspora find pathways through partnerships with a variety of actors as well as among each other (Carment and Sadjed 2017).…”
Section: Introductionmentioning
confidence: 99%